Kekuatan Hukum Resolusi Dewan Keamanan PBB Terhadap Gencatan Senjata - Bachtiar, Adjid Akbar; Anwar, Arman; Wattimena, Josina Augustina Yvonne (Faculty of Law Universitas Pattimura, 2024)
The functions of the UN Security Council are to maintain international security and order. Therefore, according to the UN Charter, all UN member states are obliged to comply with UN Security Council resolutions in settling inter-State disputes, but in reality, resolutions adopted by the United Nations Security Council are not adhered to by States, as is the UN security Council resolution on a ceasefire not observed by Israel in the Israeli-Palestinian war. The types of research used are Juridical Normative, research approaches using legislative approaches case approaches, historical approaches and comparative, and conceptual approaches. The sources of legal material are primary, secondary and tertiary legal material. The technique of collecting legal material in this research is through a library study, then qualitatively analyzed. The results of this study show that under Article 25 of the United Nations Charter, UN Security Council resolutions are binding on all UN member states in the settlement of international disputes. In the case of an Israeli-Palestinian war, Israel is obliged to comply with UN Security Council resolution No. 2728 of 2024 on a ceasefire. Israel's failure to comply with the said resolution could result in the imposition of legal sanctions on Israel, such as the suspension of its special rights as a member of the United Nations (Article 5 of the Charter), the expulsion of a State from membership of the UN (Artikel 6 of the charter), economic embargoes under Chapter VII of this Charter (Art. 41 of that Charter) and military sanctions (Act. 42 of that charter) as well as the establishment of an International Criminal Tribunal by the UN Security Council to prosecute serious human rights offenders. (Pasal 29 Piagam).